(untitled) (Research, Society and Development, 2020)
Objective: Contribute to health and nursing research, by analyzing the incidence of pressure injuries in an ICU, correlating it with the scores obtained on the Braden Scale. Method: This is a quantitative-descriptive, retrospective study carried out by collecting secondary data from the medical records of patients admitted to an adult ICU of a public hospital in the city of Natal / RN. The study sample consisted of 177 patients admitted to the ICU from March to December of the year 2019. The analysis of the results obtained was processed by means of statistical calculations, placed in absolute numbers and percentages, in the way that best demonstrated the amount sample. Results: Of the 177 hospitalized patients, 46.33% were female and 53.67% were male, with a mean age of 65.3 (± 16.50) years. Only 7.34% died. Regarding the incidence of PPL during hospitalization, a difference of 53.67% was found in men, compared to 46.33% in women. The average length of stay for patients who developed LPP was 14.51 days and for those who did not develop it was only 5.57 days. It was identified that the average of the Braden Scale scores of patients who acquired LPP during their hospitalization did not show significant variation when compared to those who did not develop LPP. Conclusion: The results allowed to trace the reality of the service studied, providing subsidies for the planning of the assistance provided and intensifying the attention to the challenges that we have in the face of the problem represented by the LPP.